Rewriting Logic and Its Applications 10th International Workshop, WRLA 2014, Held as a Satellite Event of ETAPS, Grenoble, France, April 5-6, 2014, Revised Selected Papers - Escobar, Santiago (Theoretical Computer Science and General Issues,, 2014)
This book constitutes the thoroughly refereed post-workshop proceedings of the 10th International Workshop on Rewriting Logic and its Applications, WRLA 2014, held as a satellite event of ETAPS 2014, in Grenoble, France, in March 2014. The 13 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 21 submissions. The papers address a great diversity of topics in the fields of foundations and models of RL; languages based on RL; RL as a logical framework; RL as a semantic framework; use of RL to provide rigorous support for model-based software engineering; formalisms related to RL; verification techniques for RL specifications; comparisons of RL with existing formalisms having analogous aims; application of RL to specification and analysis of distributed systems and physical systems.